2018
DOI: 10.1097/mph.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Antifungal Prophylaxis in Children With Malignancies: A Nationwide Study

Abstract: VRC prophylaxis in pediatric hematology/oncology patients appears to be well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The available paediatric data on voriconazole safety are heterogeneous, as the criteria for classifying AEs and attributing them to the drug vary widely between studies. However, the percentage of AEs we detected is similar to the values reported in other studies using the same AE classification [29,[44][45][46]72]. We mention that our recording of up to four liver function parameters, including changes with no clinical impact, may have led to an overestimation of hepatic AEs in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The available paediatric data on voriconazole safety are heterogeneous, as the criteria for classifying AEs and attributing them to the drug vary widely between studies. However, the percentage of AEs we detected is similar to the values reported in other studies using the same AE classification [29,[44][45][46]72]. We mention that our recording of up to four liver function parameters, including changes with no clinical impact, may have led to an overestimation of hepatic AEs in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Since 2014, observational studies of children with cancer or following HSCT have reported a breakthrough proven/probable IFD rate between 0 and 12% with voriconazole. [131][132][133][134] In the study reporting a 12% breakthrough rate, patients received voriconazole doses of between 5 and 10 mg/kg/day, 134 which is below the currently recommended dose (Table 7). 135…”
Section: Voriconazolementioning
confidence: 99%
“…In pediatric patients, voriconazole exposure displays substantial variability [46] and, consequently, TDM is required to maintain the plasma concentration of 1–5 mg/L [8,47,48]. In the “Voriproph” study—the largest cohort study of voriconazole chemoprophylaxis in children—the use of this agent has been well tolerated [49]. An age of <2 years is a contraindication to the use of voriconazole [8].…”
Section: Preventionmentioning
confidence: 99%